Sumanene Hexaester: An Electron-Deficient Buckybowl - Toda, Hideaki; Uetake, Yuta; Yakiyama, Yumi; Nakazawa, Hironobu; Kajitani, Takashi; Fukushima, Takanori; Sakurai, Hidehiro (Synthesis, 2019)
2,3,5,6,8,9-Hexakis(phenoxycarbonyl)sumanene, a hexasubstituted sumanene with CO2Ph groups at the peripheral aromatic carbons, was successfully prepared in good yield by Pd-catalyzed phenoxycarbonylation using a solvent of phenyl formate. Single-crystal X-ray structural analysis of this compound revealed the formation of a one-dimensional columnar structure, stacked in a staggered manner. The UV and emission spectra of this showed clear red-shifts compared with those of pristine sumanene, indicating the extension of the conjugation system.
Keywords: sumanene; buckybowls; palladium catalysis; phenoxycarbonylation; electron-deficient polycyclic aromatic hydrocarbons; columnar packing structure